2014
DOI: 10.1016/j.ecoleng.2014.07.052
|View full text |Cite
|
Sign up to set email alerts
|

Effects of evapotranspiration on treatment performance in constructed wetlands: Experimental studies and modeling

Abstract: Evapotranspiration (ET) can affect treatment performance in constructed wetlands by enhancing constituent transport through the hydrosoil where treatment reactions occur. Additionally, ET can decrease volumetric flow thereby increasing hydraulic retention time and increasing concentrations of dissolved constituents. This research aims to assess the net effects of water loss attributed to ET on constructed wetland performance and determine the significance of plant transpiration on vertical transport of constit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 20 publications
(24 reference statements)
2
9
0
Order By: Relevance
“…australis , a commonly-used species in HSSFs CWs. When comparing the findings of other authors [4849], the estimation of K c for C . alternifolius and T .…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…australis , a commonly-used species in HSSFs CWs. When comparing the findings of other authors [4849], the estimation of K c for C . alternifolius and T .…”
Section: Resultsmentioning
confidence: 81%
“…This relationship is highly significant in agronomic terms because it affects the choice of plant species in a CW in relation to our main aims. Some authors [48] claim that ET significantly affects pollutant RE in CWs and high ET values can determine higher pollutant concentrations at the outflow. In our research, in HSSFs CW(1), we found that when ET reached average values of over 20 mm d -1 , water loss increased at the outlet of the planted-units and we recorded higher BOD 5 and COD concentrations in the effluent.…”
Section: Resultsmentioning
confidence: 99%
“…However, according to Beebe [35], evapotranspiration can decrease the volumetric flow, thereby increasing the HRT and concentrations of dissolved constituents. Also investigating the effects of wind on the mixing factors on the solute tracer and hydraulic efficiency is suggested for further studies.…”
Section: Recommendationsmentioning
confidence: 99%
“…Freedman et al [12] measured similar values of 20 mm/day but observed 40 mm/day in certain times of the day. In another study, values of evapotranspiration in HSSF-CWs fluctuated between 19.5 and 40 mm/day [13]. Tuttolomondo et al [14] measured evapotranspiration in a constructed wetland in Italy and observed that on some summer days evapotranspiration reached 25-35 mm/day; this value was 20-30% of the hydraulic load.…”
Section: Introductionmentioning
confidence: 94%